Investigation on the influence of the cavitation boundaries on the dynamic behavior of planar mechanical systems with hydrodynamic bearings. (May 2016) - Daniel, Gregory Bregion; Machado, Tiago Henrique; Cavalca, Katia Lucchesi
Abstract: The characterization of lubricated revolute joints configures a topic of great interest in mechanisms and machines since there is a significant demand for its proper design in many applications. Therefore, this work proposes a solution for the evaluation of the hydrodynamic force components of the journal bearings obtained from the integration of the Reynolds equation for infinitely short bearings. The main difficulty in obtaining these hydrodynamic forces lies on adequately defining the boundary conditions of the Reynolds equation. Differently from the boundary conditions proposed in classical literature, this work presents an approach to determine the integration boundaries, i.e., the angular position in the bearing reference system where the pressure is null. Therefore, the hydrodynamic forces are calculated taking into account only the positive pressure. These angles are time dependent, and its evaluation is very important for a more accurate estimation of the hydrodynamic force components. The computer simulations are accomplished for different length–diameter ratios (L/D). From the global results, it can be concluded that the proposed approach is promising to efficiently represent the hydrodynamic conditions in bearings with L/D ratios up to 0.5. Highlights: An approach is proposed to evaluate the cavitation boundaries in hydrodynamic forces. The approach is compared with classical and numerical models. The novelty is the shifting of pressure distribution regarding the maximum thickness. The contribution to the computational costs is significant for time domain analysis. The results are promising and of high quality for infinitely short bearing.